The immune system in Alzheimer's Disease - Nogueira, Juliane Maria Alves; Maia, Thaysa Alessandra Pereira; Luiz, Nathalia Silva; Viana, Bianca Teodoro; Oliveira, Gabriela Roque de; Sá, André Luís Braghini (Seven Editora, 2024)
Alzheimer's disease (AD) is a neurodegenerative disorder characterized as a progressive and chronic disorder that leads to the destruction of cholinergic neurons. AD was studied by Alois Alzheimer, a psychiatrist and neuroanatomist, who reported the pathology as amyloidal fibrillar deposits located in the walls of blood vessels, associated with a variety of different types of senile plaques, accumulation of abnormal filaments of tau protein and consequent formation of neurofibrillary tangles (NFT), neuronal and synaptic loss, glial activation, and inflammation (Castellani et al., 2010). This article aimed to address the role of the immune system in the pathogenesis of Alzheimer's disease. This is a literature review article carried out from 2002 to 2023. The databases for search were National Library of Medicine (PUBMED), Scientific Electronic Library Online (SCIELO) and Google Scholar, using the following descriptors Neuroinflammation, Glial Cells, Amyloid Beta Peptide and Tau Protein. Innate immunity cells such as microglia and astrocytes are found close to senile plaques, evidencing the participation of elements of the immune system in neuroinflammation and neurodegeneration, consequently contributing to the progression of AD. Therefore, it is concluded that a better understanding of the action of the immune system in the disease is essential for the establishment of possible prevention and control measures. DOI:https://doi.org/10.56238/sevened2024.001-054